Pseudoperonospora cubensis development under differentiated nitrogen and potassium fertilization of Cucumis sativus - Papadaki, Anastasia A. (Cranfield University, 2009)
Cucumber (Cucumis sativus) is one of the most economically important vegetable crops worldwide and downy mildew caused by Pseudoperonospora cubensis is considered among the most destructive diseases that attack this plant. Although the effect of mineral nutrition on plant diseases for various crops has been studied, there is practically none on cucumbers. The overall objective of this study were (a) to investigate the effect of increasing inoculum concentrations of P. cubensis on downy mildew emergence on different aged cucumber leaves (b) to examine the effect of various N and K concentrations in the fertilization solution on the disease development and the leaf surface (c) to study the potential interaction of these two essential nutrients in relation with the application of a fungicide used for downy mildew control (d) to determine the disease progress with time (e) to investigate the nutritional status of cucumber tissues and substrate. A range of greenhouse experiments were conducted. Cucumbers were grown under six K (200, 300, 400, 500, 600, 700 ppm) and six N (100, 200, 300, 400, 500 and 600 ppm) fertilization regimes, in two randomized block experiments respectively. Two factorial designs, one with three levels of spore concentrations and two leaf ages and the other with two N and three K levels plus fungicide treatments were also established. Cucumber plants (Cucumis sativus L. cv. Knossou) susceptible to downy mildew were artificially inoculated with P. cubensis. Disease was digitally assessed. Statistical analysis of the obtained data indicated that the pathogen attacked leaves regardless of age. The lesion area was significantly increased with increasing spore content at low disease pressure. N concentration of 300 ppm had a positive effect on the leaf area when compared with the lower N rates. A concentration of 400 ppm K resulted in a marked increase in leaf area in relation to the other treatments although the differences were not statistically significant (P=0.05). There were indications that downy mildew was significantly decreased on the plants grown in 300 ppm N, 300 and 400 ppm K. However, N and K interaction was observed for leaf and lesion area. Thus, inhibition of infection was recorded with increasing K levels only at low N rates. The best combination for disease limitation was 200 ppm N and 400ppm K, which was found to be comparable with the fungicide used. The disease progress for downy mildew followed a cubic curve in all cases (N and K fertilization treatments, fungicide application). The importance of leaf and soil nutrient status on infection and leaf area index was also noted.